Octolasmic Octolasmis spp. parasite attack on mudcrab Scylla serrata in Tomini Bay - Suherman, Sutianto Pratama; Marjan, Rahmatiya; Lamadi, Arafik (Tomini Journal of Aquatic Science, 2022)
The present study aimed to identify the Octolasmis spp. ectoparasite's intensity and prevalence in mud crab in Pohuwato Regency. It employed survey and site observation methods with sampling technique of mud crabs in Pohuwato Regency. The research was carried out in three different sites: site 1 (Pohuwato Timur Village), site II (Bulili Village), and site III (Mootilango Village). The results showed that the parasites infesting mud crab in the three separate locations are Octolasmis angulata and Octolasmis cor. The highest intensity rate was at site III, which was dominated by Octolasmis cor. The prevalence of the parasite in sites I, II, and III was 60%, 40%, and 60% in consecutive order. Moreover, the parasite has a 100% and 46% prevalence in female and male crabs, respectively. The water quality indicator (involving temperature, pH level, and soluble oxygen) was at the appropriate rate for mud crab farming.